Anti-Nociceptive Effects of Sphingomyelinase and Methyl-Beta-Cyclodextrin in the Icilin-Induced Mouse Pain Model - Horváth, Ádám; Steib, Anita; Nehr-Majoros, Andrea; Kántás, Boglárka; Király, Ágnes; Racskó, Márk; Tóth, Balázs István; Szánti-Pintér, Eszter; Kudová, Eva; Skoda-Földes, Rita; Helyes, Zsuzsanna; Szőke, Éva (International journal of molecular sciences, 2024)
The thermo- and pain-sensitive Transient Receptor Potential Melastatin 3 and 8 (TRPM3 and TRPM8) ion channels are functionally associated in the lipid rafts of the plasma membrane. We have already described that cholesterol and sphingomyelin depletion, or inhibition of sphingolipid biosynthesis decreased the TRPM8 but not the TRPM3 channel opening on cultured sensory neurons. We aimed to test the effects of lipid raft disruptors on channel activation on TRPM3- and TRPM8-expressing HEK293T cells in vitro, as well as their potential analgesic actions in TRPM3 and TRPM8 channel activation involving acute pain models in mice. CHO cell viability was examined after lipid raft disruptor treatments and their effects on channel activation on channel expressing HEK293T cells by measurement of cytoplasmic Ca2+ concentration were monitored. The effects of treatments were investigated in Pregnenolone-Sulphate-CIM-0216-evoked and icilin-induced acute nocifensive pain models in mice. Cholesterol depletion decreased CHO cell viability. Sphingomyelinase and methyl-beta-cyclodextrin reduced the duration of icilin-evoked nocifensive behavior, while lipid raft disruptors did not inhibit the activity of recombinant TRPM3 and TRPM8. We conclude that depletion of sphingomyelin or cholesterol from rafts can modulate the function of native TRPM8 receptors. Furthermore, sphingolipid cleavage provided superiority over cholesterol depletion, and this method can open novel possibilities in the management of different pain conditions.
Keywords: membránové mikrodomény; analgetika; bolest; kationtové kanály TRPM; CHO buňky; beta-Cyclodextrins; Cell Survival; Cholesterol; Pain; Sphingomyelin Phosphodiesterase; Humans; cholesterol; sfingomyelinfosfodiesterasa; Analgesics; Pyrimidinones; pyrimidinony; lidé; HEK293 Cells; pregnenolon; zvířata; myši; lipid raft; CHO Cells; methyl-beta-cyclodextrin; pain; Mice; Cricetulus; beta-cyklodextriny; HEK293 buňky; Transient Receptor Potential; TRPM Cation Channels; Animals; sphingomyelinase; Membrane Microdomains; Disease Models, Animal; Pregnenolone; viabilita buněk; modely nemocí na zvířatech